2020
DOI: 10.31235/osf.io/hkpfj
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Suburbanization of transport poverty

Abstract: Many cities have undergone spatial re-distributions of low-income populations from central to suburban neighborhoods over the past several decades. A potential negative impact of these trends is that low-income populations are concentrating in more automobile oriented areas and thus resulting in increased barriers to daily travel and activity participation, particularly for those who are unable to afford a private vehicle. Accordingly, the objective of this paper is to analyze the links between increasing soci… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…In contrast, the high and moderate SES travel patterns were diffused with a higher number of long-distance trips, especially to visit the business districts within the city. Low SES travelers made fewer trips, possibly due to lower spatial access to opportunities, as suggested in previous studies (Wang 2003;Schleith, Widener, and Kim 2016;Allen and Farber 2020). Unavailable or inefficient transit services might have impeded long-distance travel for low SES people (Farber and Grandez 2017;Wei et al 2017).…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…In contrast, the high and moderate SES travel patterns were diffused with a higher number of long-distance trips, especially to visit the business districts within the city. Low SES travelers made fewer trips, possibly due to lower spatial access to opportunities, as suggested in previous studies (Wang 2003;Schleith, Widener, and Kim 2016;Allen and Farber 2020). Unavailable or inefficient transit services might have impeded long-distance travel for low SES people (Farber and Grandez 2017;Wei et al 2017).…”
Section: Discussionmentioning
confidence: 62%
“…Although low-income people tend to reside in the core urban areas with higher job concentrations, they are often unable to access these jobs due to limited mobility choices (Wang 2003;Wenglenski and Orfeuil 2004). Recent studies, however, have identified the shift of low-income residences from inner-city to suburban areas, resulting in longer commuting time and lower access to opportunities, especially during the last few decades (1990Schleith, Widener, and Kim 2016;Hu 2017;Allen and Farber 2020). Thus, integrated transportation and social disadvantages are more prominent in suburban areas where car ownership often becomes necessary for low-income workers to access their workplaces (Hu 2017).…”
Section: Disparities In Work Travelmentioning
confidence: 99%
“…In contrast, the high-moderate SES travel patterns were diffused with a higher number of longdistance trips, especially to visit the business districts within the city. Low SES travelers made fewer trips, possibly due to lower spatial access to opportunities, as suggested in previous studies (Wang 2003;Schleith, Widener, and Kim 2016;Allen and Farber 2020). Besides, unavailable or inefficient transit services may have impeded long-distance travel for low SES people (Farber and Grandez 2017;Wei et al 2017).…”
Section: Discussionmentioning
confidence: 62%
“…Although low-income people tend to reside in the core urban areas with higher job concentrations, they are often unable to access these jobs due to limited mobility choices (Wang 2003;Wenglenski and Orfeuil 2004). However, recent studies have identified the shift of low-income residences from inner-city to suburban areas, resulting in longer commuting time and lower access to opportunities, especially during the last few decades (Schleith, Widener, and Kim 2016;Hu 2017;Allen and Farber 2020). Thus, integrated transportation and social disadvantages are more prominent in suburban areas where car-ownership often becomes necessary for low-income workers to access their workplaces (Hu 2017).…”
Section: Disparities In Work Travelmentioning
confidence: 99%
“…Moreover, this horizontal expansion of cities resulted in ongoing challenges for transit systems that must contend with declining funding and corresponding needs for cost-cutting to cover an ever-increasing service area (30)(31)(32). Historically, sprawling urban development left low-income and vulnerable populations in deteriorating urban neighborhoods (33), but more recently, less affluent populations have been moving more into suburban areas due to gentrification and decreasing affordability of inner urban neighborhoods in many jurisdictions (34,35). As a consequence, the mobility of marginalized communities is further compromised due to limited transportation options and longer travel times, in turn limiting access to jobs, services, recreation, and social interaction (34)(35)(36).…”
Section: Introductionmentioning
confidence: 99%